2021
DOI: 10.3390/microorganisms9071347
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities of Cladonia Lichens and Their Biosynthetic Gene Clusters Potentially Encoding Natural Products

Abstract: Lichens have been widely used in traditional medicine, especially by indigenous communities worldwide. However, their slow growth and difficulties in the isolation of lichen symbionts and associated microbes have hindered the pharmaceutical utilisation of lichen-produced compounds. Advances in high-throughput sequencing techniques now permit detailed investigations of the complex microbial communities formed by fungi, green algae, cyanobacteria, and other bacteria within the lichen thalli. Here, we used amplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 108 publications
(158 reference statements)
1
8
1
Order By: Relevance
“…In contrast, the driest areas were dominated by lichens known to be associated with Trebouxia (for example, Ramalina spp.). The ability of some Cladonia species to associate with Trebouxia phycobionts (Osyczka et al, 2020;Shishido et al, 2021) might be helpful under such conditions (Romeike et al, 2002;de Vera, 2012;Candotto-Carniel et al, 2016;Leavitt et al, 2016); however, we did not find any sample containing Trebouxia.…”
Section: Phycobiont Pool Sharingcontrasting
confidence: 63%
“…In contrast, the driest areas were dominated by lichens known to be associated with Trebouxia (for example, Ramalina spp.). The ability of some Cladonia species to associate with Trebouxia phycobionts (Osyczka et al, 2020;Shishido et al, 2021) might be helpful under such conditions (Romeike et al, 2002;de Vera, 2012;Candotto-Carniel et al, 2016;Leavitt et al, 2016); however, we did not find any sample containing Trebouxia.…”
Section: Phycobiont Pool Sharingcontrasting
confidence: 63%
“…These molecules are tetrahydrodibenzofurans and have been reported in the lichens of genera Lecanora , Rhizoplaca , Leprocaulon , Phoma and Hematoma [ 40 , 41 , 42 ]. Interestingly, Shishido et al have recently reported placodiolic acid in Cladonia stellaris , C. uncialis , C. rangiferina , C. mitis and C. arbuscula [ 43 ], which corroborates its presence in C. portentosa . However, mass spectrometry cannot differentiate between placodiolic and pseudoplacodiolic acids [ 39 ].…”
Section: Discussionmentioning
confidence: 80%
“…The results showed that the NR-PKS from LFF Pseudevernia furfuracea produces depside lecanoric acid, which has never been detected from lichen thallus in nature (Calchera et al, 2019). Genome mining analysis based on a homology searching approach revealed that enzymes of grayanic acid, patulin, and betaenones A-C biosynthesis are encoded by Cladonia uncialis genome (Bertrand et al, 2018), and the result corresponds with Shishido et al (2021). The uptake of advanced analytical techniques and next-generation computational tools brought a breakthrough in lichen chemistry and resulted in the identification of various novel compounds.…”
Section: Genome Mining-based Strategymentioning
confidence: 95%